Automated functional electrical stimulation training system for upper-limb function recovery in poststroke patients. (October 2020) - Chou, Chih-Hong; Wang, Tong; Sun, Xiaopei; Niu, Chuanxin M.; Hao, Manzhao; Xie, Qing; Lan, Ning
Highlights: We developed an accelerometry system to detect the motion intention of poststroke patients for triggering FES. A visual game module was combined with this automated FES training system. This system can reduce variability in compound movements produced by poststroke patients and FES. An optimal threshold of triggering can defined for each patient for specific tasks. Abstract: Background: This paper describes the design and test of an automated functional electrical stimulation (FES) system for poststroke rehabilitation training. The aim of automated FES is to synchronize electrically induced movements to assist residual movements of patients. Methods: In the design of the FES system, an accelerometry module detected movement initiation and movement performed by post-stroke patients. The desired movement was displayed in visual game module. Synergy-based FES patterns were formulated using a normal pattern of muscle synergies from a healthy subject. Experiment 1 evaluated how different levels of trigger threshold or timing affected the variability of compound movements for forward reaching (FR) and lateral reaching (LR). Experiment 2 explored the effect of FES duration on compound movements. Results: Synchronizing FES-assisted movements with residual voluntary movements produced more consistent compound movements. Matching the duration of synergy-based FES to that of patients could assist slower movements of patients with reduced RMS errors. Conclusions: Evidence indicated that synchronization and matching duration with residual voluntary movements of patients could improve the consistency of FES assisted movements. Automated FES training can reduce the burden of therapists to monitor the training process, which may encourage patients to complete the training.